The complete sequence of the mitochondrial genome of Lantang pig (Sus scrofa). (3rd March 2016) - Ran, Mao-Liang; Liu, Zhen; Yang, An-Qi; Li, Zhi; Chen, Bin
Abstract: Lantang pig is a native breed of Guangzhou Province in China. It is the first time that the complete mitochondrial genome sequence of Lantang pig is reported in this work, which is determined through the PCR-based method. The total length of the mitognome is 16, 709 bp, which contains 2 ribosomal RNA genes, 22 tRNA genes, 13 PCGs and 1 conntrol region (D-loop region, Table 1). The total base composition of Lantang pig mitochondrial genome is 34.69% for A, 26.18% for C, 25.82% for T and 13.31% for G, in the order A>C>T>G. The complete mitochondrial genome of Lantang pig provides an important data in genetic mechanism and the evolution genomes.